FATTY LEVEL ON FRIED CHICKEN FLOUR SOLD BY FAST FOOD RESTAURANT AND STREET FOODS - Christ Kartika Rahayuningsih; Indah Lestari (poltekkes kemenkes mataram, 2018)
Abstract: Fat as a source of the greatest energy than carbohydrates and protein, and also serves as a source of vitamin A, D, E, and K. Fat consumption in excessive amounts can cause a coronary heart disease, high blood pressure, cholesterol, and atherosclerosis. Fatty level in fast food is high, such as the fried chicken and the current public interest on the fried chicken is extremely high. The objective study was to know a difference of fatty level on fried chicken at fast food restaurant and street food. This research was comparative with analysis technique against 10 fried chickens at fast food restaurants and also 10 friend chickens from street food which were taken selectively around the area of East Surabaya by using Soxhlet method that conducted at the Chemical Laboratory Unit of Surabaya Health Polytechnic. The analysis result was obtained the average value of the fatty level on fried chicken at fast food restaurant was 19.71% and street food of 25.29%. It can be concluded that there are differences in the levels of fat on fried chicken flour at fast food restaurants and street foods.Keywords: Levels of Fat; Fried Chicken Flour.